Pengaruh Pemanfaatan Aset Tetap Di BPKAD (Badan Pengelolaan Keuangan Dan Aset Daerah) Kabupaten Yahukimo Papua Terhadap Kinerja Pegawai - Karmila Selviana Rumbino; Paskah Ika Nugroho (Universitas Pendidikan Ganesha, 2021)
The purpose of this research was to examine the effect on the use of computers, vehicles, and the buildings (official residences) on the performance of the employees in Local Government Finance Office of Yahukimo Regency. This research used quantitative method and Likert scale as the measurement. The population used are fifty-seven respondents of regular and honorory employees on the Local Government Finance Office. The data collection techniques used in this study were observation, questionnaires and documentation. The variables of the study were the use of computers, vehicles, and official residences on the employees’ performance. To analyze the data, this research used multiple regression analysis with the classical assumption. The result of the research showed that the use of computers (X1) had significant and positve impacts to the employees performance. Meanwhile, the use of vehicles (X2) and official residences (X3) did not have significant impact for the employees’ performance.